Macroporous hydrogels based on 2-hydroxyethyl methacrylate. Part 6: 3D hydrogels with positive and negative surface charges and polyelectrolyte complexes in spinal cord injury repair - Hejcl, A; Lesný, P; Prádný, M; Sedý, J; Zámecník, J; Jendelová, P; Michálek, J; Syková, E (Journal of materials science. Materials in medicine, 2009)
Macroporous hydrogels are artificial biomaterials commonly used in tissue engineering, including central nervous system (CNS) repair. Their physical properties may be modified to improve their adhesion properties and promote tissue regeneration. We implanted four types of hydrogels based on 2-hydroxyethyl methacrylate (HEMA) with different surface charges inside a spinal cord hemisection cavity at the Th8 level in rats. The spinal cords were processed 1 and 6 months after implantation and histologically evaluated. Connective tissue deposition was most abundant in the hydrogels with positively-charged functional groups. Axonal regeneration was promoted in hydrogels carrying charged functional groups; hydrogels with positively charged functional groups showed increased axonal ingrowth into the central parts of the implant. Few astrocytes grew into the hydrogels. Our study shows that HEMA-based hydrogels carrying charged functional groups improve axonal ingrowth inside the implants compared to implants without any charge. Further, positively charged functional groups promote connective tissue infiltration and extended axonal regeneration inside a hydrogel bridge.
Keywords: Spinal Cord Injuries; testování materiálů; Biocompatible Materials; Nerve Regeneration; poranění míchy; Materials Testing; Guided Tissue Regeneration; Rats; potkani Wistar; methakryláty; povrchové vlastnosti; Animals; statická elektřina; Porosity; Hydrogels; Thoracic Vertebrae; výsledek terapie; biokompatibilní materiály; Rats, Wistar; zvířata; mužské pohlaví; Surface Properties; Male; hrudní obratle; Methacrylates; krysa rodu Rattus; hydrogely; Treatment Outcome; regenerace nervu; poréznost; řízená tkáňová regenerace; Static Electricity